Cancer Microenvironment: What Can We Learn from the Stem Cell Niche - Lacina, Lukas; Plzak, Jan; Kodet, Ondrej; Szabo, Pavol; Chovanec, Martin; Dvorankova, Barbora; Smetana, Karel (International journal of molecular sciences, 2015)
Epidermal stem cells (ESCs) are crucial for maintenance and self- renewal of skin epithelium and also for regular hair cycling. Their role in wound healing is also indispensable. ESCs reside in a defined outer root sheath portion of hair follicle-also known as the bulge region. ECS are also found between basal cells of the interfollicular epidermis or mucous membranes. The non-epithelial elements such as mesenchymal stem cell-like elements of dermis or surrounding adipose tissue can also contribute to this niche formation. Cancer stem cells (CSCs) participate in formation of common epithelial malignant diseases such as basal cell or squamous cell carcinoma. In this review article, we focus on the role of cancer microenvironment with emphasis on the effect of cancer-associated fibroblasts (CAFs). This model reflects various biological aspects of interaction between cancer cell and CAFs with multiple parallels to interaction of normal epidermal stem cells and their niche. The complexity of intercellular interactions within tumor stroma is depicted on example of malignant melanoma, where keratinocytes also contribute the microenvironmental landscape during early phase of tumor progression. Interactions seen in normal bulge region can therefore be an important source of information for proper understanding to melanoma. The therapeutic consequences of targeting of microenvironment in anticancer therapy and for improved wound healing are included to article.
Keywords: Neoplastic Stem Cells; Stem Cell Niche; Epidermal Cells; epidermální buňky; stem cell; Animals; nádorové kmenové buňky; fibroblasty; melanom; Wound Healing; Humans; Skin Neoplasms; Tumor Microenvironment; Epithelial Cells; Melanoma; keratinocyty; vlasový folikul; mezenchymální kmenové buňky; hojení ran; epitelové buňky; nika kmenových buněk; nádory kůže; zvířata; Keratinocytes; cancer microenvironment; Mesenchymal Stem Cells; Hair Follicle; wound healing; lidé; nádorové mikroprostředí; Fibroblasts; cancer-associated fibroblast; niche